IPTEKS SISTEM INFORMASI MANAJEMEN KEUANGAN DI DIREKTORAT JENDERAL PERBENDAHARAAN PROVINSI SULAWESI UTARA - Hidayat, Regina Putri; Kotambunan, Miranda Ellora; Saroinsong, Kezia Gabriela; Runtu, Treesje (Universitas Sam Ratulangi, 2018)
The Ministryof Finance especially the directorate general of the treasury of North Sulawesi province, is confronted with modern treasury problems. The demands of economic development are increasingly advanced, demanding a transition from the application of past culture (manual) to the stage of digital (modern) technology. The work process in the treasury sector changes, seen from the need for financial management information systems to improve the competitive advantage of modern DGT organizations in the future in increasing transparency and accountability in managing the world treasury. The emergence of treasury and state budget (SPAN) applications and agency-level financial application systems (SAKTI) as a manifestation of the implementation of financial management information systems in the Directorate General of Treasury and work units. For state treasury management to be carried out by the treasury general directorate, it can be aligned with treasury management by other countries in the world.Keywords : Financial Management Information System, SPAN, and SAKTI